Effect of Combustion Heat Release on the Stability of Confined Boundary/Mixing-layer Confluent Flow. (2015) - Zhiyong, Liu; Qing, Shang; Xiaoyong, Liu; Lisen, Fei; Fengjun, Liu
Abstract: The issue of mixing enhancement of the fuel and oxidizer in the combustor of a ramjet has received more and more attention. Various injection ways were designed and justified to improve the mixing process by producing more multiplescale vortex structures. Under the restriction of compact configuration of the combustor in an integral rocket dual combustion ramjet, a better way to enhance mixing is turning the laminar flow to turbulent flow. The present study focuses on the stability analysis of the boundary/mixing-layer confluent flow affected by the combustion heat release in the combustion chamber. Two types of basic flows are formed for linear stability analysis both from a theoretical model and numerical computation. Eigenvalue spectra and eigenfunctions are obtained and compared. The results show that the heatrelease effect stabilizes the confluent mixing flow.